Anomalous drainage of left superior venacava into left atrium - Nirmala Chandrashekar, Chandana; Seetharama Bhat, Padebettu Subramanya; Cholenahally Nanjappa, Manjunath (International Surgery Journal, 2019)
The anomalies of drainage of systemic venous communications to the heart are many. But only few cause significant hemodynamic alteration and thus, complications. When they do, they need to be surgically corrected. We report an unusual case of a patient who was found to have left pulmonary veins draining into the left superior venacava (LSVC), which in turn was opening into the roof of the left atrium that had unroofed coronary sinus morphology. Innominate vein was absent. LSVC was divided cranial to where the pulmonary veins were draining into it. Lower end was suture closed. Proximal part of the LSVC was anastamosed to left pulmonary artery.